1997
DOI: 10.1111/j.1151-2916.1997.tb02840.x
|View full text |Cite
|
Sign up to set email alerts
|

Dopant Distributions in Rare‐Earth‐Doped Alumina

Abstract: The distribution of yttrium and lanthanum dopants hason the dopant level, Al 2 O 3 grain size, and impurity content of Al 2 O 3 . been mapped in yttrium-and lanthanum-doped polycrystalline aluminas using imaging secondary-ion mass spec-The objective of this work was to map the yttrium distribution in a 1000-ppm-yttrium-doped polycrystalline Al 2 O 3 samtrometry (imaging-SIMS). Both dopants segregate to grain boundaries and pore surfaces. On average, yttrium occupies ple that has exhibited favorable creep prope… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
54
1

Year Published

1998
1998
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 103 publications
(59 citation statements)
references
References 13 publications
(5 reference statements)
4
54
1
Order By: Relevance
“…Indeed the bulk solubility is below the resolution limit of most experimental methods, the exact value being unknown although it has been reported to be lower than 80 ppm. 1 The results also qualitatively agree with DFT calculations, where H seg of −1.56 eV for 3.3 La/nm 2 were reported for the Σ3 (1 0 · 0) GB, 35 which compares well with −1.89 eV for 3.4 La/nm 2 calculated here. Another study reported H seg of −2.63 eV for 4.2 La/nm 2 at the Σ7 (−1 0 · 2) GB, 36 which again compares reasonably well with −2.34 eV for 4.3 La/nm 2 found in the present study.…”
Section: Lanthanum Segregationsupporting
confidence: 80%
See 1 more Smart Citation
“…Indeed the bulk solubility is below the resolution limit of most experimental methods, the exact value being unknown although it has been reported to be lower than 80 ppm. 1 The results also qualitatively agree with DFT calculations, where H seg of −1.56 eV for 3.3 La/nm 2 were reported for the Σ3 (1 0 · 0) GB, 35 which compares well with −1.89 eV for 3.4 La/nm 2 calculated here. Another study reported H seg of −2.63 eV for 4.2 La/nm 2 at the Σ7 (−1 0 · 2) GB, 36 which again compares reasonably well with −2.34 eV for 4.3 La/nm 2 found in the present study.…”
Section: Lanthanum Segregationsupporting
confidence: 80%
“…Control over these microstructural parameters in ceramics is typically achieved by a precise control over processing conditions and the use of dopant elements. It is well established that many dopant elements routinely added to ceramics (for example Y, La and Mg in alumina) have, due to their larger ionic size, a low bulk solubility 1 and a marked tendency to segregate to grain boundaries. 2 Once present at interfaces they can affect properties such as interface mobility and transport in the grain boundary plane.…”
Section: Introductionmentioning
confidence: 99%
“…The later of densification of ZrO 2 and La 2 O 3 -containing samples is explained by the segregation of the doping agents at grain boundaries (in solid solution and/or as precipitates). Indeed some works have already reported this segregation for all the doping agents considered [10,12,[27][28][29][30][31] during conventional sintering. Thus, the diffusion of the Al ions is reduced and grain boundary sliding is limited.…”
Section: Effect Of Sintering Temperature and Dopingmentioning
confidence: 99%
“…Most of these doping agents, due to their very low solubility in alumina, segregate at grain boundaries during the sintering. Some Secondary-Ion Mass Spectrometry (SIMS) images illustrate this phenomenon very clearly; after densification, the doping agent (MgO, La 2 O 3 and Y 2 O 3 ) is located at grain boundaries and pore surfaces [10,11]. For La 2 O 3 and Y 2 O 3 doping, the segregation leads to an inhibition of grain growth and decreases the densification rate [11].…”
Section: Introductionmentioning
confidence: 99%
“…Both Zr 4+ and La 3+ cations are larger than Al 3+ cations: their ionic radii are 0.72Å and 1.03Å, respectively for 6-fold coordination compared to 0.53Å for Al 3+ for the same coordination number. 20 Zr 4+ was found to be insoluble in an ␣-alumina lattice 21 and the bulk solubility of La 3+ is really low (∼80 cat ppm 22 ) or even lower. 4 Those doping agents therefore have a strong tendency to segregate at grain boundaries.…”
Section: Introductionmentioning
confidence: 99%